2007
DOI: 10.1096/fj.06-6884com
|View full text |Cite
|
Sign up to set email alerts
|

Circulating progenitor cells contribute to neointimal formation in nonirradiated chimeric mice

Abstract: Recent evidence suggests that bone marrow-derived cells may contribute to repair and lesion formation following vascular injury. In most studies, bone marrow-derived cells were tracked by transplanting exogenous cells into bone marrow that had been compromised by irradiation. It remains to be determined whether endogenous circulating progenitors actually contribute to arterial remodeling under physiological conditions. Here, we established a parabiotic model in which two mice were conjoined subcutaneously with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 50 publications
3
44
1
1
Order By: Relevance
“…6 Although it has been assumed that medial SMCs transdifferentiate into macrophage-like cells, 6 recent reports suggested that some synthetic SMCs with characteristics of macrophages might derive from circulating blood cells rather than from medial SMCs. 7,8 Evidence in support of this hypothesis was provided in several models of vascular diseases. By taking advantage of genetically modified mice, it was directly demonstrated that bone marrow cells home in on the damaged vessels and contribute to both vascular repair and pathological remodeling.…”
Section: Article P 3079mentioning
confidence: 81%
See 2 more Smart Citations
“…6 Although it has been assumed that medial SMCs transdifferentiate into macrophage-like cells, 6 recent reports suggested that some synthetic SMCs with characteristics of macrophages might derive from circulating blood cells rather than from medial SMCs. 7,8 Evidence in support of this hypothesis was provided in several models of vascular diseases. By taking advantage of genetically modified mice, it was directly demonstrated that bone marrow cells home in on the damaged vessels and contribute to both vascular repair and pathological remodeling.…”
Section: Article P 3079mentioning
confidence: 81%
“…14 In this regard, high-resolution confocal microscopy with z-axis analysis has been used to convincingly demonstrate that bone marrowderived cells express ␣-smooth muscle actin (␣-SMA) in neointima after wire-mediated vascular injury. 8 To rigorously identify GFP-positive cells, these studies used a plastic embedding technique to preserve the GFP fluorescence signal and to avoid the use of anti-GFP antibodies that could potentially increase the risk of false signals by nonspecific antibody binding. 7,8,16,17 Moreover, an ultrahigh-resolution immunoelectron microscopic observational study confirmed that ␣-SMA and GFP could be located within a cell.…”
Section: Article P 3079mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, multiple genes originally thought to be SMC-specific have now been identified as being expressed in alternative cell types including bone marrow cells 11,[20][21][22][23] , adventitial cells [24][25][26] , endothelial cells 27 , and more 28,29 , with the only gene currently thought to be specific to SMCs (and pericytes, a perivascular cell similar to SMCs in the microvasculature) being Myh11 17 . Indeed this ambiguity led to several papers 23,30,31 suggesting additional de novo sources of SMCs being derived from cells other than SMCs.…”
Section: Phenotypic Switchingmentioning
confidence: 99%
“…Indeed this ambiguity led to several papers 23,30,31 suggesting additional de novo sources of SMCs being derived from cells other than SMCs.…”
Section: Phenotypic Switchingmentioning
confidence: 99%